Liquid–liquid extraction of alkali cations by 18-crown-6: complexation and interface crossing studied by MD and PMF simulations. (5th January 2016) - Benay, Gael; Wipff, Georges
Abstract : The 18C6/M + Pic − complexes form and adsorb "right at the nano-interface" where 18C6 prefers the K + guest. Abstract : In order to get microscopic views of what happens at the water/chloroform interface upon selective extraction of alkali cations (M + = Na +, K +, Cs + ) by the 18-crown-6 macrocycle "18C6", we studied by MD and potential of mean force "PMF" simulations their complexation in the source phase (water) and at the interface, and the interface crossing by the different species. The binding free energies in water calculated without polarization (NO-POL) or with polarization (POL) are in good accord with the experiment. At the interface, the K + and Cs + complexes are found to be stronger than those in water, while the Na + complex is weaker. The free energy profiles for interface crossing by 18C6 and the 18C6/M + Pic − complexes (Pic − is the trinitrophenolate anion), calculated using different models, reveal a deep minimum at the interface, indicating that they are surface active, in spite of their centrosymmetrical structure. These results hint for a complexation process occurring "right at the nano-interface", a feature further supported by a POL simulation where 18C6 rapidly (<5 ns) captures K + at the interface along the dynamics. Regarding the extraction selectivity, we show that the K + complex is the most stable one at the interface, and that it is most easily transferred to the receiving phase. The complexation and extraction selectivity for K + obtained from the PMF route are also evidenced by "alchemical mutations". These simulations point the importance of the aqueous "nano-interface" for complexation, recognition and chemical reactivity in confined aqueous media.